Influência da laserterapia no alívio da dor, redução do edema e trismo pós exodontia do terceiro molar inferior: uma revisão sistemática - Souza, José Maria Ferreira de (2017)
This study aimed to perform a systematic review of the literature in order to prove the potential influence of laser therapy on the levels of pain, trismus, and edema after lower third molar extractions. PubMed (including MedLine), Scopus, Web of Science, SciELO, and Latin American and Caribbean Health Sciences (LILACS) databases were used as primary sources of studies. GoogleScholar and OpenGrey were used to search the "grey literature". The methodology of the studies selected was assessed by the MAStARI quality tool - instrument that evaluates the quality of randomized and quasi-randomized clinical trials. Quantitative results of the measuring of parameters after lower third molar extraction, such as pain, edema, and trismus, were considered main outcomes. The search performed in the electronic databases resulted in a set of 676 studies, from which 14 were selected for assessment according to eligibility criteria. Seven studies were excluded for not providing accurate quantitative measurements regarding the three clinical parameters analyzed, and one article was excluded for using a type of luminous source different from low level laser. Thus, six studies were selected for qualitative review. There was a certain degree of heterogeneity among the studies included, which showed differences regarding the following methodology requirements: study design, postoperative medication, laser therapy protocol (type of laser, power, energy, region, and frequency of irradiation), and clinical parameters analyzed (pain, mouth opening, and edema). LASER therapy was effective for reducing pain, trismus, and edema in half of the studies included, therefore, there is no sufficient conclusive evidence that low lever laser therapy is effective for that treatment. The performance of further studies with an individualized methodology pattern focusing on total randomized clinical trials is required